Backward Time of Genocide (Papers in Arts and Humanities, 2022)
In the article the notion of time in the context of the phenomena of a genocide will be analyzed. Genocide is almost never perceived by public consciousness as it progresses The present time of genocide, as it is experienced by its participants and witnesses, displays features similar to taboos. How too hard to accept for consciousness, it is forced out of the conscious memory of its surviving actors. Consequently, it seems to be a taboo for social memory too. As a result, the very recognition of the fact of genocide usually takes place many decades or even generations after the genocide itself. Przemysław Czapliński coined a term “A retrograde disaster” (Katastrofa wsteczna), as to describe Holocaust of Jews in Poland during the II world war. The point of this term is intended to describe an event that occurred mostly unnoticed and unrecognized in its importance. This was the case of Jews’ pogroms in Poland, happening during the II world war, and shortly after. The public discussion on this topic started in 2000, after Jan Tomasz Gross’ publication. National Museum of the Holodomor Genocide in Kiev was founded in 2010, even though it is devoted to memorialize the events from 1932-33. The analysis of the specificity of the time of genocide will be based on a few chosen examples.
Keywords: Holocaust; Holodomor; Congo; time; genocide